The drive-wise project: driving simulator training increases real driving performance in healthy older drivers - Casutt, Gianclaudio; Theill, Nathan; Martin, Mike; Keller, Martin; Jäncke, Lutz (Frontiers in Aging Neuroscience, 2014)
Background: Age-related cognitive decline is often associated with unsafe driving behavior. We hypothesized that 10 active training sessions in a driving simulator increase cognitive and on-road driving performance. In addition, driving simulator training should outperform cognitive training. Methods: Ninety-one healthy active drivers (62 – 87 years) were randomly assigned to either (1) a driving simulator training group, (2) an attention training group (vigilance and selective attention), or (3) a control group. The main outcome variables were on-road driving and cognitive performance. Seventy-seven participants (85%) completed the training and were included in the analyses. Training gains were analyzed using a multiple regression analysis with planned comparisons. Results: The driving simulator training group showed an improvement in on-road driving performance compared to the attention training group. In addition, both training groups increased cognitive performance compared to the control group. Conclusion: Driving simulator training offers the potential to enhance driving skills in older drivers. Compared to the attention training, the simulator training seems to be a more powerful program for increasing older drivers’ safety on the road.